2022
DOI: 10.1039/d2py00335j
|View full text |Cite
|
Sign up to set email alerts
|

Metallocene catalysts for the ring-opening co-polymerisation of epoxides and cyclic anhydrides

Abstract: The ring-opening co-polymerization (ROCOP) of epoxides and cyclic anhydrides is a versatile route to new polyesters. The vast number of monomers that are readily available means that an effectively limitless...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…It is important to highlight that this novel synthetic route has not been previously reported to date using olive-based epoxidized vegetable oils as precursors. , The first synthetic approach has been recently published by Kleij et al, where the preparation of attractive functional bio-polyesters has been achieved from the reaction between fatty acid epoxides and cyclic anhydrides . This ROCOP reaction has been extensively investigated with commercially available cyclic epoxides and anhydrides, although it requires the presence of a metal catalyst or an organocatalyst. In recent years, organocatalysts have become more popular than metal catalysts, since metal-free catalysts offer several advantages, such as higher catalyst availability at lower costs, lower sensitivity to oxygen or water, and they are more ecological and less toxic than metal-containing catalysts …”
Section: Introductionmentioning
confidence: 99%
“…It is important to highlight that this novel synthetic route has not been previously reported to date using olive-based epoxidized vegetable oils as precursors. , The first synthetic approach has been recently published by Kleij et al, where the preparation of attractive functional bio-polyesters has been achieved from the reaction between fatty acid epoxides and cyclic anhydrides . This ROCOP reaction has been extensively investigated with commercially available cyclic epoxides and anhydrides, although it requires the presence of a metal catalyst or an organocatalyst. In recent years, organocatalysts have become more popular than metal catalysts, since metal-free catalysts offer several advantages, such as higher catalyst availability at lower costs, lower sensitivity to oxygen or water, and they are more ecological and less toxic than metal-containing catalysts …”
Section: Introductionmentioning
confidence: 99%
“…Addition of the AAQ monomer presumably has a lower activation energy than CHO in this case, and a bias towards early/late incorporation is expected if the activation energies are unequal, 37 since epoxide opening is reported to be the rate-limiting step. 38,39…”
Section: Resultsmentioning
confidence: 99%
“…Addition of the AAQ monomer presumably has a lower activation energy than CHO in this case, and a bias towards early/late incorporation is expected if the activation Paper Polymer Chemistry energies are unequal, 37 since epoxide opening is reported to be the rate-limiting step. 38,39 Physical properties DSC measurements were obtained for all polymers (S3.3), from which glass transition temperatures (T g ) were obtained. As expected for small dopant quantities and comparable molecular weights, the undoped and 0.2 mol% doped PA-CHO copolymers showed no significant variation in their T g , lying between 138 and 140 °C.…”
Section: Synthesis Of Luminophore Monomers and Coloured Polymersmentioning
confidence: 99%
“…The polymerization of vinylcyclohexene oxide (VCHO) with PA was also achieved using amine-bis(phenolate) chromium(III) complexes [30] as well as chromium complexes with an [OSSO]-type bis(phenolato) dianionic ligand in the presence of DMAP as a cocatalyst [31]. In 2022, Ward et al reported the copolymerization of CHO or VCHO and PA using metallocene catalysts, with polymerization performance in terms of molecular masses and conversion of PA being somewhat modest in comparison with that achieved using DMAP alone [32]. Recently, Urban [33] reported advances in stimuli-responsive commodity polymers obtained from functionalized polyesters with cleavable bonds, such as disulfide, thioketal, or β-selenylated carbonyl linkages.…”
Section: Methodsmentioning
confidence: 99%